Applicability of the MADIT-CRT Response Score for Prediction of Long-Term Clinical and Arrhythmic Events by QRS Morphology. (September 2020) - Younis, Arwa; Goldenberg, May; Kutyifa, Valentina; Polonsky, Bronislava; Mcnitt, Scott; Zareba, Wojciech; Golovchiner, Gregory; Aktas, Mehmet K.; Barsheshet, Alon
Abstract : Supplemental Digital Content is available in the text.